Wojenna rozsypanka - Wantuch, Wiesława (Polonistyka. Innowacje, 2015)
The article shows an example of classroom work in junior high school with Milosz’s and Szymborska’s poems about war. The comparative analysis and different interpretations of its extensions in the work with poetic texts is dealt here in the presence of military themes in popular culture. "Reading through a magnifying glass" can induce a young receiver to a more vigilant behavior in relation to the images of war offered also by Polish cinema.